Aerodynamic Simulation of the MARINTEK Braceless Semisubmersible Wave Tank Tests. (September 2016) - Stewart, Gordon; Muskulus, Michael
Abstract: Model scale experiments of floating offshore wind turbines are important for both platform design for the industry as well as numerical model validation for the research community. An important consideration in the wave tank testing of offshore wind turbines are scaling effects, especially the tension between accurate scaling of both hydrodynamic and aerodynamic forces. The recent MARINTEK braceless semisubmersible wave tank experiment utilizes a novel aerodynamic force actuator to decouple the scaling of the aerodynamic forces. This actuator consists of an array of motors that pull on cables to provide aerodynamic forces that are calculated by a blade-element momentum code in real time as the experiment is conducted. This type of system has the advantage of supplying realistically scaled aerodynamic forces that include dynamic forces from platform motion, but does not provide the insights into the accuracy of the aerodynamic models that an actual model-scale rotor could provide. The modeling of this system presents an interesting challenge, as there are two ways to simulate the aerodynamics; either by using the turbulent wind fields as inputs to the aerodynamic model of the design code, or by surpassing the aerodynamic model and using the forces applied to the experimental turbine as direct inputs to the simulation. This paper investigates the best practices of modeling this type of novel aerodynamic actuator using a modified wind turbine simulation tool, and demonstrates that bypassing the dynamic aerodynamics solver of design codes can lead to erroneous results.